2008
DOI: 10.1103/physrevlett.100.081301
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Growth of Firehose and Mirror Fluctuations in Astrophysical Plasmas

Abstract: In turbulent high-beta astrophysical plasmas (exemplified by the galaxy cluster plasmas), pressure-anisotropy-driven firehose and mirror fluctuations grow nonlinearly to large amplitudes, deltaB/B approximately 1, on a time scale comparable to the turnover time of the turbulent motions. The principle of their nonlinear evolution is to generate secularly growing small-scale magnetic fluctuations that on average cancel the temporal change in the large-scale magnetic field responsible for the pressure anisotropie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
175
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(184 citation statements)
references
References 27 publications
8
175
0
1
Order By: Relevance
“…[9] There is evidence that mirror modes have important effects on energetic particle diffusion [Tsurutani et al, 1999] and electron thermal conductivity [Schekochihin et al, 2008]. What is more, it has also been suggested that mirror modes observed at 1 AU might even be an indicator of the presence of ion-cyclotron waves in the solar corona [Russell et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…[9] There is evidence that mirror modes have important effects on energetic particle diffusion [Tsurutani et al, 1999] and electron thermal conductivity [Schekochihin et al, 2008]. What is more, it has also been suggested that mirror modes observed at 1 AU might even be an indicator of the presence of ion-cyclotron waves in the solar corona [Russell et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…However, the shearing or expansion process that drove the plasma through the instability boundary in the first place, must ultimately become important again once quasilinear relaxation has pushed the system sufficiently close back to marginality. When such continued driving is accounted for, asymptotic theory [33,34] predicts secular growth of perturbations as δB/B ∝ t 1/2 up to δB/B = O(1) (cf. [35]), a very different outcome from steady-state, lowamplitude saturation.…”
mentioning
confidence: 99%
“…In this Letter, we show that weakly nonlinear mirror modes in such conditions do not saturate quasilinearly at a steady, low amplitude either, but continue to grow secularly as δB/B ∝ t 2/3 . To do this, we introduce a new asymptotic theory in the spirit of earlier theoretical work [33,34,42], in which the combined effects of weak collisionality, large-scale shearing, quasilinear relaxation [32,43,44], particle trapping [45][46][47][48] and finite ion Larmor radius (FLR) are all self-consistently retained.…”
mentioning
confidence: 99%
“…Observational evidences for fire-hose instabilities (FHI) occurring in space plasma environments have been reported 1,2 and the applications of FHI to astrophysical systems have also been proposed. 3,4 Theoretical studies of FHI have been mostly based on the kinetic theory and particle simulations [5][6][7][8][9][10][11][12] due to the issue of energy closure to the hydromagnetic equations in gyrotropic plasmas. In recent years, we have attempted to study the FHI using the so-called double-polytropic MHD and Hall MHD models and compared the results with the Vlasov theory and kinetic simulations.…”
Section: Introductionmentioning
confidence: 99%